Studi Keanekanekaragaman Jenis Burung dan Pemanfaatan Ruang Vertikal di Blok Selok Hutan Lindung RPH Sumbermanjing Kulon - Ngudang, Sanherib Umbu Kabobu; Kurniawan, Iwan; Farida, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The Birds a crucial role in maintaining the balance of forest ecosystems, serving as seed dispersers, pollinators, and pest controllers, as well as being indicators of environmental quality. The Selok Block Protect Forest in the RPH Sumbermanjing Kulon is a critical habitat requiring scientific study of its bird diversity, protecting endemic species and maintaining the forest's ecological function. The objectives of this study were to determine bird species diversity, vegetation status, and the use of vertical space by birds. This research was conducted in the RPH Sumbermanjing Kulon Protect Forest Area, Sumberbening Village, Bantur District, Malang Regency. The research was conducted in July 2025. Two observation routes were used using the Point Count method. The data obtained were analyzed descriptively and quantitatively using the Shannon-Winner species diversity index (H'). to determine the diversity of bird species. The use of vertical space was analyzed qualitatively descriptively by visualizing images of vegetation strata in the Selok Block Area of the RPH Sumbermanjing Kulon Protect Forest. Based on the results of the Shannon Winer index (H') diversity of bird species in the Selok Block, a value of 2.458 was obtained, indicating that diversity is classified as moderate. Vegetation strata utilized by birds on both paths are ground cover strata, shrubs, saplings, and poles.